“We Cannot Write About Complicity Together”: Limits of Cross-Caste Collaborations in Western Academy - Patel, Shaista Aziz; Da Costa, Dia (Engaged Scholar Journal)

(untitled) (University of Saskatchewan, 2022)
Grounded in a friendship that began in the academy, we write together to problematize collaborative writing across our distinct caste positionalities. Writing as caste-oppressed Pakistani Muslim settler (Patel) and dominant caste Indian settler (Da Costa), we write primarily across caste power lines to focus on the failure in our own efforts at collaborative writing. This article, initially meant to focus on our complicities in white settler colonialism in its present form, reflects on the detours we undertook to arrive at this place of certainty that “we cannot write about our complicity together.” Specifically, we reconsider some assumptions underlining prominent methodological commitments of transnational collaborative writing across uneven locations in, for, and beyond the academy. Collaborative writing has been championed for its capacity to generate dialogue across disagreements, praxis grounded in social change, a challenge to the academy’s notions of individual knowledge-production and merit, and as a means of holding people across hierarchies accountable to structures of violence that remain at work within social movements and collective struggles. Considering the contours of what Sara Ahmed (2019) calls structural “usefulness” of collaborative writing to the colonial and neoliberal academy, we use historical and life-writing approaches to make caste violence legible in order to refuse the cover that collaborative writing provides to dominant caste South Asians engaged in research with Indigenous, Black, Muslim, caste-oppressed and multiply and differentially colonized communities. Our purpose is to foreground the historical and ordinary violence of caste as it shapes North American academic relationships, intimacies, and scholarship, in order to challenge the assumption that caste-privileged South Asian scholars of postcolonial and transnational studies in western academia are best poised to collaborate with Indigenous, Black, other racialized, and Dalit scholars and actors toward a decolonial, abolitionist, and anti-casteist feminist praxis. While focusing on writing across caste lines, our analysis can also be read as offering a space to engage ethically with complexities informing collaborative projects across differential horizontal and vertical power relations informed by race, class, gender, sexuality, citizenship, north/south and other differences. In the process of writing this article, we have also paid particular attention to our citational practices.